TINGKAT MOTIVASI MAHASISWA PENDIDIKAN JASMANI KESEHATAN DAN REKREASI UNIVERSITAS RIAU ANGKATAN 2019 DALAM MELAKUKAN OLAHRAGA DI RUMAH SELAMA PANDEMI COVID-19 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to find out how big the level of motivation of students in Physical Education, Health and Recreation, University of Riau Class of 2019 was in doing sports at home during the Covid-19 pandemic. The method used by the researcher is a questionnaire/questionnaire method via google forms. Questionnaires were given to students of Physical Education, Health and Recreation, University of Riau Class of 2019, totaling 75 students. From the results of the research process to data processing, starting with data collection for testing the research instrument as many as 49 people in the Physical Education Health and Recreation Study program, University of Riau stated that the 28 statements were valid which was stated by r count > from r table (0.281) and reliability test with Cronbach's Alpha value of 0.874. After the researchers conducted a trial of the research instrument, the researchers then distributed questionnaires to 75 samples, namely Physical Education, Health and Recreation, University of Riau Batch 2019 to produce data that was used as a benchmark as a discussion of research results. The results showed that (1) intrinsic factors with a percentage of 72.3% and (2) extrinsic factors with a percentage of 54.25%. Thus, it can be concluded that the Motivation Level of Physical Education and Recreational Health and Recreation Students at the University of Riau Class of 2019 in Doing Sports at Home During the Covid-19 Pandemic is said to be very high with a percentage of 78.75%.Key Words: Student Motivation, Sports at Home, Covid-19